Sosialisasi Peraturan Pemerintah Republik Indonesia Nomor 11 Tahun 2021 Tentang Badan Usaha Milik Desa - Yorry Hardayani (TRANSFORMASI : JURNAL PENGABDIAN PADA MASYARAKAT, 2022)
The fulfillment of the general welfare and economy of the village should be the backbone of a solidly constructed. The development of village economic resilience requires awareness and joint effort of all components including at every macro, meso, micro level even at every level that can be uniquely defined. Village Owned Enterprises (BUMDes) is a village economic institution / agency that is incorporated and owned by the Village Government which is managed independently, economically and professionally. The purpose of socialization is to increase the knowledge and competence of village devices in the management of BUMDes, especially in Sunda Kelapa Village, Pondok Kelapa District of Central Bengkulu Regency. Socialization about BUMDes is carried out by the method of providing knowledge material about BUMDes as well as discussions and questions and answers. Bumdes management in Sunda Kelapa Village has been implemented quite well by the village government. There is already a clear management structure and has been incorporated. But the management of BUMDes has not been too maximal because the benefits of BUMDes have not been too felt by the community. Therefore, assistance or coaching from related parties or government agencies needs to be done so that BUMDes in Sunda Kelapa Village can continue to run well in accordance with Government Regulations